Growth kinetics of diazotrophic Bacillus sphaericus UPMB10 cultured using different types and concentrations of carbon and nitrogen sources - Ooi, T. C.; Ariff, Arbakariya; Mohd Saud, Halimi; Shamsuddin, Zulkifli (Malaysian Society for Microbiology, 2008)
Growth kinetics of newly isolated diazotrophic Bacillus sphaericus UPMB10 grown in various carbon (lactate, acetate, glycerol, malate, fructose, xylose and sucrose) and nitrogen (glutamate, yeast extract, arginine, hystadine, glycine, polypeptone, tryptophan, lysine, NH4Cl and urea) sources was investigated using 2 L stirred tank fermenter. The highest growth was obtained in a medium containing lactate as a carbon source, which gave the highest maximum cell concentration of 2.30 g/L, which is corresponding to maximum viable cell count of 4.60 x 109 cfu/mL. However, the highest cell yield (1.06 g cell/g carbon consumed) was obtained in cultivation using glycerol though slightly lower maximum viable cell count was obtained (3.22 x 109 cfu/mL). In addition, cost for the production of live cell using glycerol was about 15 times lower than the cost using lactate. Growth performance of this bacterium when yeast extract was used as a nitrogen source was comparable to the use of pure amino acid. The medium containing 1.8 g/L glycerol and 2 g/L yeast extract was suggested as optimal for growth of this bacterium, which gave carbon to nitrogen ratio (C/N) of 10:1. The maximum viable cell count obtained in cultivation using optimised medium in 2 L stirred tank fermenter was 3.34 x 109 cfu/mL and the cells maintained its capacity for N2 fixation at 18 nmol C2H2/h.mL.